KONSTRUKSI BERITA RESPON PARTAI DEMOKRAT TENTANG DUET ANIES– MUHAIMIN DALAM PILPRES 2024 PADA TVONENEWS.COM DAN CNNINDONESIA.COM - Ainul Nur Mufidah Lutfiah; Abidin, Sholihul (SCIENTIA JOURNAL, 2024)
In this research, the data collection method was carried out through three main techniques, namely observation, literature study, and documentation regarding news related to News Construction of the Democratic Party's Response to the Anies – Muhaimin Duet in the 2024 Presidential Election on the tvonenews.com and cnnindonesia.com sites. Research It adopts a qualitative research method, which is in accordance with Bogdan and Taylor's definition explained by Moleong. From the results of the framing analysis, it can be seen that tvonenews.com's news construction regarding the Democratic Party's response to the Anies-Muhaimin duet in the 2024 presidential election tends to be objective. This is demonstrated by the four framing analysis structures created by Zhongdang Pan and Kosicki, which show balance in the presentation of news data. Meanwhile, the media cnnindonesia.com is less objective, because cnnindonesia.com speaks more from the perspective of the Chairman of the Democratic Party Assembly, Susilo Bambang Yudhoyono. According to tvonenews.com and cnnindonesia.com, this media reality construction depicts that the Democratic Party is disappointed because Anies Baswedan left AHY, who had previously been approved to be the presidential and vice presidential candidate